2006
DOI: 10.1097/01.ccm.0000201896.45809.e3
|View full text |Cite
|
Sign up to set email alerts
|

Does dopamine administration in shock influence outcome? Results of the Sepsis Occurrence in Acutely Ill Patients (SOAP) Study*

Abstract: This observational study suggests that dopamine administration may be associated with increased mortality rates in shock. There is a need for a prospective study comparing dopamine with other catecholamines in the management of circulatory shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
205
2
23

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(242 citation statements)
references
References 29 publications
12
205
2
23
Order By: Relevance
“…High-molecular-weight hydroxyethyl starch solutions (≥200 kDa) appear to be deleterious in terms of renal function (203,204); low-molecular-weight starch solutions, on the other hand, may improve renal tissue oxygenation by decreasing blood viscosity (205) and reducing vascular resistance, along with preventing starch molecule accumulation in the renal tubules and the disturbance of glomerular hemodynamics (206). Likewise, because low doses of dopamine are ineffective in terms of prevention or treatment of acute renal failure (201,207), norepinephrine (208) and vasopressin (209) are probably the drugs of choice for improving function in the renal macrocirculation and microcirculation. Because reaching supraphysiological hemodynamic values are at least doubtful (210) and may be harmful (211,212), the optimal fluid volume that should be given remains difficult to estimate.…”
Section: Therapeutic Implications and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…High-molecular-weight hydroxyethyl starch solutions (≥200 kDa) appear to be deleterious in terms of renal function (203,204); low-molecular-weight starch solutions, on the other hand, may improve renal tissue oxygenation by decreasing blood viscosity (205) and reducing vascular resistance, along with preventing starch molecule accumulation in the renal tubules and the disturbance of glomerular hemodynamics (206). Likewise, because low doses of dopamine are ineffective in terms of prevention or treatment of acute renal failure (201,207), norepinephrine (208) and vasopressin (209) are probably the drugs of choice for improving function in the renal macrocirculation and microcirculation. Because reaching supraphysiological hemodynamic values are at least doubtful (210) and may be harmful (211,212), the optimal fluid volume that should be given remains difficult to estimate.…”
Section: Therapeutic Implications and Perspectivesmentioning
confidence: 99%
“…Activated protein C (APC), an endogenous vitamin Kdependent serine protease with multiple biological activities, may meet these criteria (207). Along with antithrombotic and profibrinolytic properties, APC can reduce the chemotaxis and interactions of leukocytes with activated endothelium (214).…”
Section: Therapeutic Implications and Perspectivesmentioning
confidence: 99%
“…Los dos contrincantes históricos han sido dopamina y noradrenalina. Varios estudios han reportado resultados preocupantes en relación a dopamina, mostrándola como una droga con menor acción vasopresora, con mayor incidencia de arritmias por su acción beta adrenérgica y asociada con un peor desenlace en pacientes con shock séptico [33][34][35][36] . No obstante, la evidencia era fundamentalmente circunstancial, por lo que se requería de mejores estudios para alcanzar una conclusión definitiva.…”
Section: En Presencia De Hipotensión Y/ounclassified
“…The complexities of ventriculo-arterial coupling and the variability of systemic to regional haemodynamic coherence are still incompletely understood and challenging to monitor, rendering their associated management arguably overly simplistic and targeting pattern recognition rather than the idiosyncrasies of single patients. The incidence of circulatory failure in patients admitted in the ICU is around 30% [1]. Atrial fibrillation may be observed in as high as 25% of critically ill patients [2] and is associated with increased length of ventilation and mortality [3].…”
mentioning
confidence: 99%
“…The evolution of electronic medical records, the potential to analyse big data and the development of new *Correspondence: antoine.vieillard-baron@aphp.fr 1 Intensive Care Unit, Section Thorax-Vascular Disease-Abdomen-Metabolism, Assistance Publique-Hôpitaux de Paris, University Hospital Ambroise Paré, 92100 Boulogne-Billancourt, France Full author information is available at the end of the article clinical trial designs using more extensive networks put cardiovascular studies in critically ill patients of a similar magnitude to cardiological cohorts within reach. Alongside such progress, clinical governance and audit are likely to improve with potential for more rapid and comprehensive guidelines to be embedded in practice.…”
mentioning
confidence: 99%